PELAKSANAAN MANAJEMEN KURIKULUM 2013 PADA TINGKAT SEKOLAH DASAR DI KECAMATAN TANJUNG EMAS - Vera Defyanti (IAIN Batusangkar, 2016)
Implementation of Management Curriculum 2013 at the Elementary School in the Tanjung Emas District. The purpose of this study to describe the management curriculum at the elementary school 2013, and knowing the causes of curriculum policy 2013 and its implications for management in the primary school curriculum.From the results of the study revealed that the implementation of the 2013 curriculum management in primary schools have not fully load a fundamental change of the curriculum. Fundamental change of curriculum in 2013 was the planting of religious attitudes and social behavior, learning developed through thematic integrative, Scientific approach, which requires authentic teacher assessment measure all competency as attitudes, skills, and knowledge based processes and outcomes, as well as the compulsory extracurricular Scout. This means that schools still require the maximum development of the 2013 curriculum management planning, implementation, controlling and evaluation of the curriculum should be implemented as well as possible.Keywords: management curriculum, curriculum 2013